2021
DOI: 10.3389/fneur.2021.628557
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the Acute Phase Systemic Immune–Inflammation Index in Patients With Intracerebral Hemorrhage

Abstract: Background and Purpose: The systemic immune–inflammation index (SII) is a novel prognostic index in various diseases. We evaluated the predictive value of SII in patients with intracerebral hemorrhage (ICH).Methods: Patients with primary spontaneous ICH were enrolled. SII was constructed based on peripheral platelet (P), neutrophil (N), and lymphocyte (L) and defined as P*N/L. In addition to admission testing, acute phase SII was collected to analyze the potential dynamic change. Poor outcome was defined as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown the clinical significance of SII in hemorrhagic stroke. An increased SII obtained at admission or obtained at 1 day after initial hemorrhage is associated with poor functional outcomes in patients with spontaneous intracerebral hemorrhage ( 22 , 23 ). However, secondary intracerebral hemorrhage, including SAH, was ruled out in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the clinical significance of SII in hemorrhagic stroke. An increased SII obtained at admission or obtained at 1 day after initial hemorrhage is associated with poor functional outcomes in patients with spontaneous intracerebral hemorrhage ( 22 , 23 ). However, secondary intracerebral hemorrhage, including SAH, was ruled out in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In ICH, patients with supratentorial spontaneous ICH early SII index was an independent predictor of poor outcome at time of hospital discharge [ 58 , 61 ]. In another study, SII was associated with 90-day functional outcome [ 62 ]. In patients submitted to IVT, an increased 24-h SII was associated with poor functional outcome [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al. ( 16 ) demonstrated that SII, particularly in the acute phase (day 1), is highly correlated with 90-day functional outcomes in ICH patients. This index can be used to predict the prognosis.…”
Section: Discussionmentioning
confidence: 99%